2015
DOI: 10.1002/jcb.25035
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Activity of Systemically Administered Curcumin on Oral Cancer in the 4-Nitroquinoline 1-Oxide Model

Abstract: Curcumin has therapeutic potential in preventing several types of cancer, including colon, liver, prostate, and breast. The goal of this study was to evaluate the chemopreventive activity of systemically administered curcumin on oral carcinogenesis induced by 4-nitroquinolone-1-oxide (4-NQO). A total of 50 male albino rats, Rattus norvegicus, (Holtzman), were divided into five groups (n = 10 per group). Four of these groups were exposed to 50 ppm 4-NQO in their drinking water ad libitum for 8 or 12 weeks, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Previous chemoprevention studies have evaluated natural products such as guggulipid and curcumin, as well as targeted small molecules such as erlotinib and celecoxib. (9, 14, 20) Despite some success in pre-clinical models, clinical trials have failed to demonstrate chemopreventive efficacy of celecoxib or erlotinib in patients with oral pre-malignant lesions, with no significant improvement in clinical response and unacceptable toxicities associated with chronic treatment. (10, 12) Thus, there remains an unmet clinical need for an effective chemopreventive strategy in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous chemoprevention studies have evaluated natural products such as guggulipid and curcumin, as well as targeted small molecules such as erlotinib and celecoxib. (9, 14, 20) Despite some success in pre-clinical models, clinical trials have failed to demonstrate chemopreventive efficacy of celecoxib or erlotinib in patients with oral pre-malignant lesions, with no significant improvement in clinical response and unacceptable toxicities associated with chronic treatment. (10, 12) Thus, there remains an unmet clinical need for an effective chemopreventive strategy in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous chemoprevention studies have tested compounds that lead to inhibition of STAT3 signaling, including curcumin (14, 25) and erlotinib. (9) Erlotinib is a tyrosine kinase inhibitor that indirectly inhibits STAT3 via EGFR blockade, while curcumin inhibits multiple kinases upstream of STAT3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin has garnered attention in Western medicine because of its antiinflammatory, antioxidant, anticancer, and chemopreventive properties (Belcaro et al, 2014;Guo et al, 2015;Panahi et al, 2014). Evidence obtained from in vitro and in vivo studies indicated that curcumin has a therapeutic potential in preventing and treating several types of cancer (Arumuggam et al, 2015;de Paiva Goncalves et al, 2014;Maruta, 2014).…”
Section: Introductionmentioning
confidence: 99%